8x+1=12x-3

Simple and best practice solution for 8x+1=12x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+1=12x-3 equation:


Simplifying
8x + 1 = 12x + -3

Reorder the terms:
1 + 8x = 12x + -3

Reorder the terms:
1 + 8x = -3 + 12x

Solving
1 + 8x = -3 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
1 + 8x + -12x = -3 + 12x + -12x

Combine like terms: 8x + -12x = -4x
1 + -4x = -3 + 12x + -12x

Combine like terms: 12x + -12x = 0
1 + -4x = -3 + 0
1 + -4x = -3

Add '-1' to each side of the equation.
1 + -1 + -4x = -3 + -1

Combine like terms: 1 + -1 = 0
0 + -4x = -3 + -1
-4x = -3 + -1

Combine like terms: -3 + -1 = -4
-4x = -4

Divide each side by '-4'.
x = 1

Simplifying
x = 1

See similar equations:

| 14-2*6+7= | | -8-5x=2+x | | 8x(5+6)=2 | | 15=b+12 | | 6(6x+10)=-3 | | 3y-1=7 | | 4(x-1)=1 | | 7x(11+7)=-2 | | 5w-6=4 | | 4(x-1)+7=8 | | 7-3(y-2)=19 | | -3e=24 | | 6x+4=9x+10 | | 9+2*8= | | 2y+3x=17 | | 18x-(8x-8)=67 | | -2c+9=19 | | -8x+3=29+2x | | 6(2x+2)=-6 | | 2x^2-5x-20=0 | | 4+8x-3x-1-2= | | 7n-8=3n+4 | | -10y-2y=64 | | -16x^2-x+225=0 | | 8+7x-5-2x= | | 2x+6=3x+8 | | 7a+2=-26 | | 5(6x+3)=3(2x-2) | | x^4-5x^3=14x^2 | | 6b+10=-2 | | 7x-3x^2=2 | | 7x-36=6x+3 |

Equations solver categories